Why agricultural production in sub-Saharan Africa remains low compared to the rest of the world – a historical perspective. (1st October 2020) - Bjornlund, Vibeke; Bjornlund, Henning; Van Rooyen, Andre F.
ABSTRACT: Agricultural production in sub-Saharan Africa has, in recent times, remained lower than the rest of the world. Many attribute this to factors inherent to Africa and its people, such as climate, soil quality, slavery and disease. This article traces the role of agriculture through history and argues that these are not the main reasons. Before the arrival of European traders, complex agricultural systems existed, which supported food security, manufacturing and trade. External interference manipulated these systems in pursuit of export crops. Independence has not fundamentally changed this; resource and wealth extraction continue to inhibit economic development for Africans in Africa.